Visualizing the cultural landscape gene of traditional settlements in China: a semiotic perspective - Zui Hu; Strobl Josef; Qingwen Min; Min Tan; Fulong Cheng (Heritage Science, 2021)
Abstract China has a deep traditional culture and a long history, and is rich in traditional settlements (designated as “Famous Historic-Cultural Villages/Towns”, “Chinese Traditional Villages” by Chinese Government). To help people develop these traditional settlements to achieve the great goal of Chinese National Rejuvenation, Chinese scholar put forward the Cultural Landscape Genes of Traditional Settlements (CLGTS) in 2003. Since then, CLGTS theory has been employed to solve the issues of Chinese traditional settlements, such as the identification and regionalization of cultural landscape genes in traditional settlements, and the understanding of architectural features. Although CLGTS theory has made great strides in many application fields, there is still a lack of scientific findings in exploring the symbol mechanism from a perspective of semiotics. To explore this, we firstly examined the core features of CLGTS through a dialectical perspective. We analyzed two features of CLGTS in depth. First, CLGTS is the dialectical combination of macro settlement image and micro cultural factors of traditional settlements, material appearance and inherent traditional cultural implications, overall features and local self-renewal mechanisms, qualitative and quantitative methods, superiority of cultural factors and rich cultural connotation. Second, CLGTS is famous for its nonlinearity, self-organization, and self-iteration due to various spatial shapes and complex structures. Based on the above, we first proposed the concept of Symbolization Method of CLGTS (SM-CLGTS). Then, we further explored the key features, classification methods, and corresponding representation methods of CLGTS symbols. Finally, by using Visual C#.net program language, we developed a prototype system of the Traditional Landscape Genetic Symbol Database (TLGSD) to create and centrally manage CLGTS symbols. Test results show that TLGSD can meet the needs of constructing a CLGTS symbol database for a given region. This study is of great significance to explore and contribute to visualizing the CLGTS symbols.